Analysis of Production Factors and Allocative Efficiency In Tilapia Fish Hatchery In Tanjung District, Tabalong Regency - Sari Mahrita; Erma Agusliani; Emmy Sri Mahreda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Tilapia fish hatchery business in Tabalong Regency has an important role as a seed provider for tilapia fish cultivation activities. The study aims to analyze the allocation of production factors in tilapia fish hatchery to achieve optimal conditions. This study was conducted in Tanjung District, Tabalong Regency, South Kalimantan Province using a purposive sampling method because the area is a center for tilapia fish hatchery, with a population of 61 farmers who met the respondent criteria, namely aged over 15 years, willing to be interviewed, and are tilapia fish farmers. The production factors of pond area, number of broodstock, feed, labor, and fertilizer significantly influence tilapia seed production in Tanjung District, Tabalong Regency. Partially, the factors with significant influences are the number of broodstock and feed, with positive elasticities of 0.633 and 0.417, respectively. The results of allocative efficiency show that the number of broodstock in tilapia fish NPMXi/PXi is 29.583 > 1, so the use of the number of broodstock is not efficient and still needs to be increased, while the feed in tilapia fish NPMXi/PXi is 0.045 < 1, so the use of feed is not efficient because it is excessive and needs to be reduced. Thus, optimal production can be achieved by increasing the number of broodstock appropriately and controlling feed use so that production costs are more efficient and the production results of tilapia fish seeds increase.